Extrachromosomal viral DNA produced by transcriptionally active endogenous viral elements in non-infected banana hybrids impedes quantitative PCR diagnostics of banana streak virus infections in banana hybrids. (2nd November 2021) - Ricciuti, Emeline; Laboureau, Nathalie; Noumbissié, Guy; Chabannes, Matthieu; Sukhikh, Natalia; Pooggin, Mikhail M.; Iskra-Caruana, Marie-Line
Abstract : The main edible and cultivated banana varieties are intra- and interspecific hybrids of the two main Musa species, Musa acuminata and Musa balbisiana, having diploid genomes denoted A and B, respectively. The B genome naturally hosts sequences of banana streak virus (BSV) named endogenous BSV (eBSV). Upon stress, eBSVs are identified as the origin of BSV infection for at least three BSV species, causing banana streak disease. For each of the three species, BSV and eBSV share >99.9 % sequence identity, complicating PCR-based diagnosis of viral infection in the B genome-containing bananas. Here, we designed a quantitative PCR-based method to only quantify episomal BSV particles produced, overcoming the limitation of eBSV also being detected by qPCR by using it as a 'calibrator'. However, our results revealed unexpected variation of eBSV amplification in calibrator plants composed of a clonal population of 53 replicating virus-free banana hybrids with the same AAB genotype. Our in-depth molecular analyses suggest that this calibrator variation is due to the variable abundance of non-encapsidated extrachromosomal viral DNA, likely produced via the transcription of eBSVs, followed by occasional reverse transcription. We also present evidence that accumulation of viral transcripts in AAB plants is downregulated both at post-transcriptional and transcriptional levels by an RNA interference mechanism that keeps the plants free of virus infection. Finally, we recommend that such eBSV amplification variation be taken into account to establish a quantitative viral diagnostic for banana plants with the B genome.